Individual variation in fungiform papillae density with different sizes and relevant associations with responsiveness to oral stimuli. (December 2019) - Piochi, M.; Pierguidi, L.; Torri, L.; Spinelli, S.; Monteleone, E.; Aprea, E.; Arena, E.; Borgogno, M.; Cravero, M.C.; Galassi, L.; Gatti, E.; Lozano, L.; et al.
Highlights: Individuals greatly vary in fungiform papillae pattern (density and size) on the tongue. The FP density decreases in all diameter sizes with aging. Limited gender effects were found on FP density for specific diameter sizes. No association was found between PROP status and FP densities in different diameter sizes. Uniform and small size FP were associated with increased responsiveness to oral stimuli. Abstract: The association of fungiform papillae (FP) density with responsiveness to oral sensations is controversial. It has been speculated that FP size is a relevant feature for oral responsiveness, thus partially accounting for inconsistencies between FP density and oral responsiveness. This study aims to evaluate factors affecting the number of FP with different diameter sizes (age, gender, PROP status) and to explore the relevant associations with responsiveness to oral sensations in water solutions and food products. Three-hundred-fifty subjects participating in the Italian Taste project were involved, balanced for gender (53% females) and age class (18–30, 35%; 31–45, 35%; 46–60, 30%). The automated image analysis of tongue pictures was used to detect FP and count their frequencies, distinguishing 11 diameter size classes (range from 0.3 to 1.05 mm). Frequencies were converted into FP densities (FP/cm 2 ) for each size. Taste responsiveness in water solutions (sour, bitter, salty, umami, sweet, astringent, pungent) and in three food products with varied intensity of target sensations (pear juice for sourness; bean purée for saltiness; tomato juice for pungency) was measured. Density of FP from all size classes decreased with age. Females showed higher FP density in size of 0.78–0.84 mm diameter, and males in the size of 0.44–0.49 mm. PROP status did not significantly affect the density of FP in any size class. Principal Component Analysis on individual FP density values of the 11 classes allowed identifying four subject groups with different FP patterns: high density and large diameter (HighLarge), high density and small diameter (HighSmall), low density and large diameter (LowLarge), low density and small diameter (LowSmall). FP pattern groups significantly affected oral responsiveness, the highest responsiveness was associated to the uniform pattern characterized by low density and small size FP.